Delinquency behavior from Adverse Childhood Experience - Ernawati, Linda (Faculty of Psychology, Universitas Negeri Yogyakarta, 2023)
Delinquent behavior includes breaking the rules to committing criminal acts. There are many factors behind delinquency behavior, both internally and externally. Externally, this behavior cannot be separated from events that occurred in childhood, especially events experienced in the family environment or as an Adverse Childhood Experience (ACE). Of the 6 delinquency groups in the Child Correctional Institution, this study intends to see what ACEs are experienced by juvenile delinquency perpetrators. The research subjects were taken as a whole as many as 72 teenagers. Data collection using the Adverse Childhood Experience scale. Data analysis using ANOVA. The results show that there is no difference in Adverse Childhood Experience in the 6 delinquency groups. From the average obtained, the group for drug crimes, sexual crimes, murder, theft, and child protection experienced 5 types of Adverse Childhood Experience, and the brawling group experienced 4 types of Adverse Childhood Experience. The types of Adverse Childhood experiences that are often experienced by juvenile delinquents are emotional neglect and physical neglect. 68% of teenagers who carry out delinquent behavior come from families whose parents work as laborer and traders